ECOLOGICAL AND SYSTEMATIC ANALYSIS OF THE ALGOFLORA OF THE TUYABO‘GOZ RESERVOIR - Temirov Abdumovlon Abduvaliyevich (Modern American Journals, 2025)
This article examines the composition of algae (phytoplankton) in the Tuyabuguz Reservoir and their ecological characteristics. During the research, the algal species found in the reservoir were identified, and their systematic composition, seasonal development dynamics, and relationship with key environmental factors - temperature, light, water transparency, and gas regime - were analyzed.
Keywords: Reservoir, algae (algaflora), ecological characteristics, research, systematic composition, seasonal development, temperature, light, water transparency, gas regime.